Comparative Review of Adoption in Croatia and Slovenia: Similarities, Differences and Efficiency - Guštin, Matko (Medicine, Law & Society, 2022)
The similarities between the adoption institute in Croatia and Slovenia are caused primarily by historical aspects. However, many contemporary links have influenced the regulation of the institute of adoption – Croatia and Slovenia are signatories of many international documents and are, at the European level, members of the Council of Europe and the European Union. The author gives a comparative overview of adoption according to the preconditions for adoption, required consents, legal effects, and procedural aspects. This paper also analyzes compliance with the revised 2008 European Convention on Adoption, which neither of the two countries has signed, although they almost fully accept its guidelines. In addition, the relevant cases against Croatia and Slovenia concerning adoptions decided by the European Court of Human Rights are analyzed, as well as the effects of these decisions on their legislation. To gain a more complete insight into the effectiveness of adoption, the paper also analyzes statistical data related to the adoption in Croatia and Slovenia.